Pendidikan Islam Multikultural dalam Prespektif Azyumardi Azra - halim, abdul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
Multicultural Islamic Education is an educational model that is believed to be an effective means of instilling multicultural values ​​into students so that they are expected to accept and respect all kinds of differences that exist as a necessity and sunnatullah. Azyumardi Azra is a reformer in the world of Indonesian education who is concerned in discussions about pluralism and multiculturalism so that his thoughts on the multicultural Islamic education model are very important to study. This study aims to describe Multicultural Islamic Education in the perspective of Azyumardi Azra. There are 2 focus of study in this research include; First, the concept of Multicultural Islamic Education in Azyumardi Azra's perspective. Second, the values ​​of Multicultural Islamic Education in Azyumardi Azra's perspective. This research approach is a qualitative research and belongs to the type of literature research, which requires processing of philosophical and theoretical meaning related to values. The results of this study indicate that; First, Multicultural Islamic Education in Azyumardi Azra's perspective is oriented to the formation of human beings who are faithful, devoted, become competent experts, accept the cultural diversity that exists in response to demographic and cultural changes in the community. The purpose of the multicultural Islamic education curriculum is directed at the formation of human beings who have Islamic wasathiyah insights. The content of the multicultural Islamic education curriculum must contain; 1) have an element of wisdom by reaping peace. 2) able to narrate the national aspect. 3) covers multicultural subjects such as; tolerance, ethno-cultural, religion, mediation, human rights, democracy and plurality. The relevant method is active learning. While the urgency is as a strategic step to overcome the phenomenon of extremism and radicalism. Second, the values ​​of Multicultural Islamic Education according to Azyumardi Azra include; 1) Tasaamuh/tolerance, 2) Wasathiyah/moderate, 3) Takriim/mutual respect, 4) Humanity/humanity, 5) Peace.